Cap-Independent Translational Control of Carcinogenesis - Walters, Beth; Thompson, Sunnie R. (Frontiers in Oncology, 2016)
Translational regulation has been shown to play an important role in cancer and tumor progression. Despite this fact, the role of translational control in cancer is an understudied and under appreciated field, most likely due to the technological hurdles and paucity of methods available to establish that changes in protein levels are due to translational regulation. Tumors are subjected to many adverse stress conditions such as hypoxia or starvation. Under stress conditions translation is globally down regulated through several different pathways in order to conserve energy and nutrients. Many of the proteins that are synthesized during stress in order to cope with the stress use a non-canonical or cap-independent mechanism of initiation. Tumor cells have utilized these alternative mechanisms of translation initiation to promote survival during tumor progression. This review will specifically discuss the role of cap-independent translation initiation, which relies on an internal ribosome entry site (IRES) to recruit the ribosomal subunits internally to the messenger RNA (mRNA). We will provide an overview of the role of IRES-mediated translation in cancer by discussing the types of genes that use IRESs and the conditions under which these mechanisms of initiation are used. We will specifically focus on three well studied examples: Apaf-1, p53, and c-Jun, where IRES-mediated translation has been demonstrated to play an important role in tumorigenesis or tumor progression.